Peran Literasi Keuangan dalam Memutuskan Pembelian Logam Mulia pada Masyarakat Tambun Selatan - Arief Teguh Nugroho; Sunita Dasman; Yuhaning Praborini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Gold is a precious metal that is loved by many people. Precious metals are no stranger to socienty,in general, precious metals that are known to public are precious metals in the form of jewelry. The research objective was to determine the effect of product knowledge, brand image, and lifestyle on Antam's precious metal purchasing decisions. This study uses a quantitative research model, with a sampling method using non-probablity sampling with a purposive sampling technique. The number of samples in this study was 96 which was rounded off to 100 respondents. Methods of data collection by means of observation, interviews, literature study, and distributing questionnaires through the Google Form. . The data analysis method uses validity tests, reliability tests, and multiple linear regression analysis using SPSS version 25 program assistance. The results of this study indicate that there is a significant positive effect of product knowledge on purchasing decisions for Antam's precious metal consumers, there is a significant positive influence for brand image on purchasing decisions for Antam's precious metal consumers, and there is no significant influence of lifestyle on purchasing decisions for Antam's precious metal consumers. From the results of the research findings that have been carried out, there are two hypotheses that have an effect, and there are one hypotheses that state that they have no effect.